Overcoming multidrug resistance with nanomedicines. (February 2015) - Ganoth, Assaf; Merimi, Keren Cohen; Peer, Dan
<x xml:space="preserve">Abstract</x> Introduction: Cancer remains the leading cause of death worldwide. Numerous therapeutic strategies that include smart biological treatments toward specific cellular pathways are being developed. Yet, inherent and acquired multidrug resistance (MDR) to chemotherapeutic drugs remains the major obstacle in effective cancer treatments. Areas covered: Herein, we focused on an implementation of nanoscale drug delivery strategies (nanomedicines) to treat tumors that resist MDR. Specifically, we briefly discuss the MDR phenomenon and provide structural and functional characterization of key proteins that account for MDR. We next describe the strategies to target tumors using nanoparticles and provide a mechanistic overview of how changes in the influx:efflux ratio result in overcoming MDR. Expert opinion: Various strategies have been applied in preclinical and clinical settings to overcome cancer MDR. Among them are the use of chemosensitizers that aim to sensitize the cancer cells to chemotherapeutic treatment and the use of nanomedicines as delivery vehicles that can increase the influx of drugs into cancer cells. These strategies can enhance the therapeutic response in resistant tumors by bypassing efflux pumps or by increasing the nominal amounts of therapeutic payloads into the cancer cells at a given time point.